A Digital Innovation for the Personalized Management of Adherence: Analysis of Strengths, Weaknesses, Opportunities, and Threats - Hein, Anna-Elisa; Vrijens, Bernard; Hiligsmann, Mickael (Frontiers in Medical Technology, 2020)
Introduction: Personalized medicine and management of adherence are potential solutions for the suboptimal use of medicines. Digital medication management innovations currently under development combine both aspects. This research aims to investigate facilitators and barriers for the translation of digital innovations for personalized medicine and adherence management into clinical practice from the policymaker and regulator perspective. Methods: A mixed-method study was used combining a scoping review to identify main interests, semi-structured interviews (n=5) with representatives of European health policymaking and regulatory organizations, and a supplementary literature review to investigate key subthemes. The SWOT-analysis was used for the qualitative analysis. Results: The literature reviews and the qualitative interviews suggested that digital solutions can facilitate the personalized management of medications and improve quality and safety, especially as the openness for digital health solutions is increasing. Digital solutions may, on the other hand, add complexity to the treatment, which can be perceived as a potential barrier for their uptake. As more multidisciplinary and participative structures are emerging, digital solutions can promote the implementation of new services. Nevertheless, change progresses slowly in the task-oriented structures of health systems. Integration of digital solutions depends on all stakeholders’ willingness and abilities to co-create this change. Patients have different capabilities to self-manage their medical conditions and use digital solutions. Personalization of digital health solutions and integration in existing service structures is crucial to ensure equality among population segments. Developments in the digital infrastructure, although they are partly slow and not well-aligned, enable the implementation of innovations in clinical practice leading to further advances in data generation and usage for future innovations. Discussion: This study suggests that digital solutions have the potential to facilitate high-quality medication management and improve adherence to medications, enable new service structures, and are essential to drive further innovations in health care. Nevertheless, increasing the self-responsibility of patients can have undesirable effects on health outcomes, especially within vulnerable population segments. Digital health solutions can be an opportunity to optimize the use of medicines and thus their efficiency. Well-conceived development and implementation processes are needed to also realize improvements in equality and solidarity within health systems.